The Biological properties of the compost produced from Sawani Composting Plant - Belkher, Salah (International Journal of Scientific Research and Management (IJSRM), 2022)
The biological properties (pathogen content) of four compost, composite samples produced from Al Sawani Composting Facility were studied during December 2004, January, February and March 2005, and the results indicated that these samples contained pathogenic bacterial species such as Enterobacter, Escherichia.Spp, Salmonella. Spp, Vibrio. Spp, Proteus. Spp, Klebsiella. Spp, Shigella. Spp, Citrobacter. Spp, Serratia. Spp, Staphylococcus. Spp, Pseudomonas. Spp, Streptococcus faecalis, bacteria forming - spores.Fungal species that are pathogenic to humans and plants, include Aspergillus flavus, Aspergillus niger, Penicillium Sp, Cladosporium Sp, Geotrichum Sp, Ulicladium Sp.The results were compared with the international specifications or standards for the quality of compost produced from municipal solid waste, it became clear and all samples were found to be biologically contaminated with bacterial and fungal pathogens in the humans, animals, and plants.  This can be attributed to the failure of the operational process to produce mature compost which should end through the final treatment stage, as it is essential to destroy all pathogens.Regarding the detection of nematodes, ascaris and some parasites, the tests did not show any positive results confirming their presence in the samples studied.